Factors Influencing Patients' Decisions to Use Health Services for Retreatment at Putri Hijau Medan TK II Hospital in 2023 - Prayoga, Muhammad Arif; Theo, Deli; Nasution, Ramadhani Syafitri (PROMOTOR, 2024)
Patient behavior as consumers in utilizing health services, including the decision to seek re-treatment, is influenced by several factors such as the quality of doctor/nurse services, distance, facilities, and speed of service. This study aims to analyze the factors that influence patients' decisions to utilize health services for repeat treatment. The research method used was quantitative with a cross-sectional design, carried out at the Putri Hijau Level II Hospital in Medan. A sample of 247 people was selected using the accidental sampling method from a population of 3,946 people. Data analysis used univariate, bivariate chi-square, and multivariate approaches with multiple logistic regression at a 95% confidence level. The research results show that the quality of doctor/nurse services, distance, facilities, and speed of service have a significant influence on the patient's decision to seek treatment again. Meanwhile, factors such as age, gender, education, and employment do not have a significant effect. The most dominant factor is facilities, where respondents who feel that hospital facilities are good have a higher chance of undergoing repeat treatment. This research concludes that factors such as the quality of doctor/nurse services, distance, facilities, and speed of service have a significant influence on patients' decisions in utilizing health services for re-treatment at Putri Hijau Level II Hospital in Medan. It is recommended that the hospital allocate a budget to improve facilities that are still lacking and improve new service facilities to increase public confidence in seeking treatment again.